Does Investor Sentiment Affect Islamic Stock Prices? Evidence From Indonesia - Farah Amalia; Nindi Riyana Saputri (Universitas Tidar, 2022)
The Islamic finance industry in Indonesia has grown rapidly in the last decade, one of which is marked by the number of sharia stocks. Sharia stocks, based on the underlying principle, prohibit the involvement of investor sentiment which is often used as a consideration in investment decisions because there are elements of tadlees in it. This study examines the influence of investor sentiment on islamic stock prices index. This study aims to analyze whether Islamic stock price indices are influenced by investor sentiment. The representation of Islamic stock price indices are Indonesia Sharia Stock Index (ISSI) and Jakarta Islamic Index (JII). This study utilizes ARCH/GARCH analysis to determine whether there is an influence of investor sentiment on Islamic stock prices. The statistical tool used is e-views 12.0 program. The research findings stated that investor sentiment influences Jakarta Islamic Index (JII) but doesnt influence Indonesia Sharia Stock Index (ISSI). The difference in the results between the two Islamic stock indices can be explained by the different constituents and criteria for selecting Islamic stocks